(3GdfXQjI GdeMGSHjI (B/s - (3gfOQjcSf, EdOhf Ss; (3NdjaI, CHh RjO ceGd s ((3GdGScfOQjI(B: s (3LGeYI GdEScfOQjI(B, s, 1990)
(3jVe efGgL GdfXQjI GdeMGSHjI, JWhQ GdfXQjI GdeMGSHjI, GdeONd GdGSJfHGWj GdeYjGQj, CShGb QCS GdeGd GdcaGAI, GSJNOGe GdGaQGO ddeMGSHI hGdJTZjd GdPgfj ddeYdheGJ, GdSjGSI GdeMGSHjI, eaGgje GdONd dCZQGV GdJbGQjQ GdeGdjI, GdGjQGOGJ hGdeUQhaGJ GdecGSH hGdNSGFQ, GdJbQjQ Yf BKGQ JZjQGJ GdCSYGQ, GdCUhd hbjGSgG, GdCUhd GdLGQjI hGdGdJRGeGJ GdLGQjI, GdeNRhf, GdCUhd GdKGHKI, GdGSJgdGc, GdCUhd ZjQ GdedehSI hGdGSJKeGQGJ ZjQ GdLGQjI, GdGdJRGeGJ hbjGSgG, Mbhb GdedcjI, GdGaUGM aj GdJbGQjQ GdeGdjIs
(3GdWHYIGdEfLdjRjI(B1982s
Keywords: (3GdeMGSHIs; (3GdeMGSHI(B- (3fXQjGJs